Mobility and migration in ancient Mesoamerican cities - Arnauld, Marie-Charlotte 1948-; Beekman, Christopher Stockard; Pereira, Grégory (University Press of Colorado, 2021)
"Studies on population migration in central Mexico and the Maya region among Classic, Epiclassic, and Postclassic Mesoamerican societies within the framework of urbanization and de-urbanization showing that mobility and migration reveals about the formation, development, and decline of town- and city-based societies in the ancient world"--
Keywords: Regionale Mobilität; Maya; Binnenwanderung; Mesoamerika; Indians of Mexico / Migrations; Indians of Central America / Migrations; Migration, Internal / Mexico; Migration, Internal / Central America; Indians of Mexico / Urban residence; Indians of Central America / Urban residence; Indians of Mexico / Antiquities; Indians of Central America / Antiquities; Migration, Internal; Central America; Mexico; Aufsatzsammlung